2016
DOI: 10.1590/1807-1929/agriambi.v20n9p777-782
|View full text |Cite
|
Sign up to set email alerts
|

Daily and seasonal patterns of CO2 fluxes and evapotranspiration in maize-grass intercropping

Abstract: A B S T R A C TStudies that investigate the relationships between CO 2 fluxes and evapotranspiration (ET) are important for predicting how agricultural ecosystems will respond to climate changes. However, none was made on the maize-grass intercropping system in Brazil. The aim of this study was to determine the ET and CO 2 fluxes in a signal grass pasture intercropped with maize, in São João, Pernambuco, Brazil, in a drought year. Furthermore, the soil water storage (SWS) and leaf area index (LAI) were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
(30 reference statements)
0
2
0
3
Order By: Relevance
“…Absorbing more CO 2 based on the consumption of unit water will greatly improve water use efficiency. Previous studies reported that there were differences in the carbon sequestration and water consumption capacities of ecosystems due to differences in crops, leading to significant differences in their WUE [4,25,32,47,48]. Therefore, spring maize, as a typical C4 plant, exhibits relatively higher water use efficiency compared to cotton at both leaf and ecosystem levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Absorbing more CO 2 based on the consumption of unit water will greatly improve water use efficiency. Previous studies reported that there were differences in the carbon sequestration and water consumption capacities of ecosystems due to differences in crops, leading to significant differences in their WUE [4,25,32,47,48]. Therefore, spring maize, as a typical C4 plant, exhibits relatively higher water use efficiency compared to cotton at both leaf and ecosystem levels.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of crops is comprehensively influenced by various factors, such as photosynthetic active radiation, temperature, precipitation, soil moisture, plant development, and leaf area index. These factors affect the carbon sequestration capacity of farmland ecosystems, which is significantly lower in the early and late stages of crop growth than in the period of high yield [31,32]. The main influencing factors of the same crop vary with different time scales.…”
Section: Introductionmentioning
confidence: 99%
“…Os ecossistemas de regiões áridas e semiáridas, como a Caatinga no Nordeste do Brasil, desempenham um papel importante no ciclo global do dióxido de carbono, sendo esses ecossistemas considerados em algumas épocas do ano como sumidouros de CO2 (Machado et al, 2016;Campos et al, 2019;Mendes et al, 2020;Mendes et al, 2021;Bezerra et al, 2022;. Por esta razão ecossistemas como a Caatinga devem estar em pauta quando o assunto é a mitigação dos efeitos das mudanças climáticas (Luyssaert et al, 2007).…”
Section: Introductionunclassified
“…O manejo adequado da irrigação requer o conhecimento da evapotranspiração da cultura, que varia em função da disponibilidade de água no solo; ambos estritamente relacionados com o rendimento das plantas (Machado et al, 2016;Ribeiro et al, 2018). A evapotranspiração (ET) pode ser obtida por diversos métodos, desde de medições diretas, a partir de lisímetros (Oberholzer et al, 2017;Jayaram et al, 2018;Xu et al, 2018;Munitz et al, 2019;Rafi et al, 2019) ou de técnicas de correlação dos turbilhões -Eddy Covariance (Machado et al, 2016;Silva et al, 2017b;Ribeiro et al, 2018;Campos et al, 2019;Marques et al, 2020;Wang et al, 2020), a medições indiretas, como os dos balanços de energiarazão de Bowen (Lima et al, 2017;Buttar et al, 2018;Vanomark et al, 2018;Pozníková et al, 2018) e hídrico (Souza et al, 2013;Souza et al, 2015;Liu et al, 2016;Tie et al, 2018;Hussain et al, 2019;Thapa et al, 2020). Vários pesquisadores propuseram o método do balanço hídrico no solo para estimar a ET na palma forrageira (Silva et al, 2015;Barbosa et al, 2017a;Barbosa et al, 2017b;Morais et al, 2017;Pereira et al, 2017;Lima et al, 2018b), devido o mesmo apresentar resultados confiáveis e ter menor custo que os métodos do balanço de energia e da correlação dos turbilhões.…”
Section: Introductionunclassified